Sustaining identities in the face of competing norms: returners' identity work. - Kutzer, Roxanne (Cranfield University, 2018)
Management and organization studies indicate that motherhood can change women’s working lives and that the transition to motherhood contributes to the leaky pipeline for female talent. The extant literature suggests that women manage tensions between cultural norms for ‘good mothers’ and ‘ideal workers’ by developing a consistent approach, such as prioritising their maternal identities over their worker identities or trying to segment the two identities to limit conflict. However, the suggestion that women can manage tensions between their maternal and worker identities utilising one strategy implies stability in these identities that is not evident in the everyday practices of working mothers. Drawing on a qualitative study of German women’s experiences of returning to professional and managerial roles within a manufacturing company following parental leave, I describe the identity work returners engage in to sustain their maternal and worker identities in the face of competing norms for mothers and workers. The findings indicate that returners engage in dialectic identity work, which is the purposeful and situationally-emergent effort returners expend to construct coexisting maternal and worker identities. This study extends previous research by highlighting the instability and incoherence in maternal and worker identities following the return to work -- differentiating between the strategies returners describe using in response to identity challenges upon workplace re- entry and the dialectic identity work tactics that facilitate situationally-appropriate identity responses. Applying Kreiner et al.’s (2015) identity elasticity construct to individual identities, this study demonstrates how returners maintain maternal and worker identities that are shifting and incoherent. This study also extends our understanding of women’s experiences in returning to work by revealing the influence of the length of parental leave taken and prior return to work experience on returners’ identity work.
Keywords: Women returners; intensive mothering; ideal worker norm; parental leave; maternity leave; working mothers